Unsteady Natural Convection of Sodium Alginate Viscoplastic Casson Based Based Nanofluid Flow over a Vertical Plate with Leading Edge Accretion/Ablation - Hussanan, Abid; Sidra, Aman; Zulkhibri, Ismail; Mohd Zuki, Salleh; Widodo, Basuki (Akademi Baru, 2018)
The present study explores the impact of viscous dissipation on unsteady two dimensional boundary layer flow of viscoplastic Casson ferrofluid over semi-infinite vertical plate with leading edge accretion/ablation. Tiwari-Das model is used to incorporates the effects of volumetric fraction of nanoparticles. Sodium alginate (SA) is taken as viscoplastic Casson based fluid containing Fe2O3 ferroparticles. Formulated differential equations along with relevant boundary conditions are solved numerically by Runge Kutta Fehlberg fourth-fifth order (RKF45) method. The effects of sundry parameters such as the Prandtl number, Eckert number, Casson parameter, accretion/ablation parameter, and nanoparticle volume fraction on velocity and temperature fields are investigated for both Rayleigh-Stokes and Blasius flat plate problems. Thermal boundary layer thicknesses for Blasius flat plate problem is thinner than Rayleigh-Stokes problem.